Glyceraldehyde-3-phosphate dehydrogenase gene from Zymomonas mobilis: cloning, sequencing, and identification of promoter region. - Conway, T (1987)
The gene encoding glyceraldehyde-3-phosphate dehydrogenase was isolated from a library of Zymomonas mobilis DNA fragments by complementing a deficient strain of Escherichia coli. It contained tandem promoters which were recognized by E. coli but appeared to function less efficiently than the enteric lac promoter in E. coli. The open reading frame for this gene encoded 337 amino acids with an aggregate molecular weight of 36,099 (including the N-terminal methionine). The primary amino acid sequence for this gene had considerable functional homology and amino acid identity with other eucaryotic and bacterial genes. Based on this comparison, the gap gene from Z. mobilis appeared to be most closely related to that of the thermophilic bacteria and to the chloroplast isozymes. Comparison of this gene with other glycolytic enzymes from Z. mobilis revealed a conserved pattern of codon bias and several common features of gene structure. A tentative transcriptional consensus sequence is proposed for Z. mobilis based on comparison of the five known promoters for three glycolytic enzymes.